2010
DOI: 10.1021/jz100558r
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Sites and Binding Nature of CO2 in Prototypical Metal−Organic Frameworks: A Combined Neutron Diffraction and First-Principles Study

Abstract: We report a detailed study of CO2 adsorption in two important metal−organic framework (MOF) compounds (Mg-MOF-74 and HKUST-1). In both MOFs, the open metal ions were identified as the primary binding sites through neutron diffraction measurements. The relatively strong metal−CO2 binding was attributed to an enhanced electrostatic interaction, and vibrational mode analysis shows that the adsorbed CO2 molecule is strongly attached through one of its oxygen atoms while the rest of the molecule is relatively free.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
289
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(325 citation statements)
references
References 23 publications
34
289
1
1
Order By: Relevance
“…an O-C-O angle differing from 180 • . 8 In this work we also allow non-linear distortion of the CO 2 molecule, and we find that the relaxed CO 2 molecules are only slightly bent after adsorbed within MOF74, featuring an O-C-O angle of 179.25 • in Zn-MOF74 and 178.97 • in Mg-MOF74.…”
Section: A Structure and Binding Energymentioning
confidence: 78%
See 2 more Smart Citations
“…an O-C-O angle differing from 180 • . 8 In this work we also allow non-linear distortion of the CO 2 molecule, and we find that the relaxed CO 2 molecules are only slightly bent after adsorbed within MOF74, featuring an O-C-O angle of 179.25 • in Zn-MOF74 and 178.97 • in Mg-MOF74.…”
Section: A Structure and Binding Energymentioning
confidence: 78%
“…For example, it has been shown that using unsaturated metal centers, such as MOF74 with open Mg, Mn, Zn, Ni, Cu, or HKUST-1 with Cu, results in higher absorption density for hydrogen and faster absorption at small partial CO 2 pressures, the latter of which is highly desirable for CO 2 capturing applications. [5][6][7][8][9][14][15][16][17][19][20][21][22] It has further been shown that iso-structural MOFs with different open metal centers can have very different absorption rates at low pressure. 7 In particular, the electronically similar metal centers Mg and Zn result in a much faster CO 2 uptake rate in Mg-MOF74 than in Zn-MOF74 at a pressure smaller than 0.1 atm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The charge and dipole interactions were found to dominate in this system. Although, it has been shown that the electrostatic interactions dominate when CO2 is near a cation [36] and vdW interactions are prominent when CO2 is far from the cation (away from its equilibrium position) [37]. Nevertheless, we incorporated the vdW-DFT scheme in the energetic calculations to compare with DFT.…”
Section: Methodsmentioning
confidence: 99%
“…[ 58,59 ] While it was hypothesized from high initial isosteric heats (−47 kJ mol −1 ), [ 40 ] derived from gas-adsorption measurements, that CO 2 molecules preferentially bind at the open metal site, other methods such as diffraction, IR and Raman spectroscopy, and density functional theory (DFT) have been used to afford direct evidence of the location and orientation of CO 2 molecules binding within the pore. [60][61][62][63][64][65] From neutron powder diffraction (NPD) data, it has been found that CO 2 molecules bind in an "end-on" orientation with Mg-O(CO 2 ) distances and angles that range from 2.24 to 2.39 Å and 125 to 144°, respectively, depending on the CO 2 loading level. [ 60 ] These results agree well with DFT-derived Mg-O(CO 2 ) distances and angles computed at the B3LYP-D level to be 2.31 Å and 129°, respectively.…”
Section: Co 2 Adsorption In the M 2 (Dobdc) Seriesmentioning
confidence: 99%